2003
DOI: 10.1149/1.1593047
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anodic Oxidation Current of Flattened p-Type Si(111) Surface in Aqueous Solution

Abstract: The current-voltage curve of an atomically flattened hydrogen-terminated p-Si(111) surface is studied in 0.1 M ammonium borate solution in a potential region from the onset of the anodic current to about 3 V vs. Ag/AgCl. Three anodic current peaks are observed in this potential region. A deconvolution of the current-voltage (I-V) curve revealed that these three peaks are related to the oxidation of three Si monolayers from the surface. The current due to the oxidation of the first monolayer consists of two com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In the course of time, the inability to reduce the porosity and improve the dielectric properties of these oxides has caused a decrease of interest in this topic. In the last decade, just a few articles devoted to this topic have appeared in the literature [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of time, the inability to reduce the porosity and improve the dielectric properties of these oxides has caused a decrease of interest in this topic. In the last decade, just a few articles devoted to this topic have appeared in the literature [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the voltammograms it is clearly observed that the first anodic oxidation steps of Si(111)-H electrodes (black curve) are represented by two current peaks at around 0 (peak A I ) and 1.0 V (peak A II ). The first maximum (A I peak) with a charge density around 1.0 mC cm –2 corresponds to the oxidation of the topmost silicon atoms with rupture of Si–Si and Si–H bonds. , This charge density is approximately the one calculated for the oxidation of two layers of Si atoms of an ideal Si(111) surface, although in the present case the Si-H electrodes have certain surface roughness on the atomic scale. (See Section 3.3.…”
Section: Resultsmentioning
confidence: 50%
“…The anodic pulse was applied for 100 s, which is enough time to pass a charge density of 1.0 mC cm −2 able to oxidize only a few layers of silicon surface. 31 Cyclic voltammetry in the anodic potential region (between −0.6 and 1.5 V) at 0.02 V s −1 was employed for electrochemical characterization of different silicon surfaces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current transient is sensitive to the annealing process, which suggests that current can be a good tool for the evaluation of the SijSiO 2 interface structure. It may be interesting to note that the hydrogen-terminated Si surface is anodically oxidized to form the SijSiO 2 interface in solution not containing HF, and this current is sensitive to the structure of the hydrogenterminated Si surface [30,31]. This phenomenon is apparently opposite to the current transient, both phenomena are informative about the surface and interface structures of Si.…”
Section: Introductionmentioning
confidence: 99%